THE STRATEGY OF ACADEMIC ADMINISTRATION TOWARDS THE EDUCATIONAL STANDARDS OF THE BASIC EDUCATION LEVEL OF PHRAPARIYATTIDHAMMA SCHOOLS IN THE NORTHEAST - (Thiamkaew), Phrakhrukasempanyapirak; Sirisuthi, Chaiyuth; Choosorn, Phayuth (Journal of Buddhist Anthropology, 2021)
The Objectives of this research article were to 1) study the present condition, desirable condition and the need for the development of academic administration to the quality in accordance with the basic educational standards 2) develop the strategy of academic administration towards the quality standards of the Basic Education level of PhraPariyattidhamma School in the Northeast. Mixed method Research by the used of quantitative and qualitative research methods. The samples used in this quantitative research were 341 administrative, teachers, and staff per person. The statistic used were percentage, frequency, mean, standard deviation. The order of demand index is necessary. Matrix analysis as for the qualitative research the interviewee group consisted of 9 the experts for a group interview. The tools used were group interviewing and group discussion. The findings were as follows: 1) The current condition was at a high level. Desirable condition was at the highest level. In respect of the requirements were necessary, in descending order: in the evaluation and academic transfer comparison, development of learning processes, development and use of educational technology media, research and learning development, educational supervision, and the development of educational institutions curriculum. 2) There were 6 academic management strategies: 2.1) Accelerate the development knowledge, ability of measurement, assessment according to real conditions, and academic transfer comparison of teachers and educational personnel 2.2) Support the development of learning processes to be efficient and focus on learners as important 2.3) Support the development of innovative media and educational technology 2.4) Promote and support research and development of learning 2.5) Develop an internal supervision system aimed at encouraging teachers to organize a learner - centered teaching and learning process. 2.6) Develop an educational institution curriculum focusing on the quality of learners in all areas that are suitable for the context of the school and community.